Knowledge and Practice of Food Handlers on Food Safety and Health: a Cross Sectional Study in One of Tehran's Districts. - Ehsan Haghi; fariba razeghi; Ahmad Ahmadi; Gholamreza Jahed Khaniki (Shahid Beheshti University of Medical Sciences, 2019)
Background: The people involved in food preparation play a major role in contaminating it due to improper food handling. According to a report of the World Health Organization, more than one third of the population in developing countries become ill from food-borne diseases also  The European Food Safety Authority report, about 48.7% of food-borne diseases are caused by eating food provided in public places. The goal of this study was to examine the knowledge and practice of 390 food handlers in one of Tehran's district using questionnaires. Methods: The reliability of the questionnaires were measured using Cronbach's alpha and Intra-class correlation obtained from  test and re-test in an interval of 10 days. The reliability and validity index of the questionnaires were found to be above 70%, which were acceptable. Results: The results showed that there is a lack of knowledge in the field of thorough cooking of food, storing it at the right temperature, proper defrosting of frozen materials, and hygienic practice. Although the practice of the participants were evaluated to be at a good level, in some cases, such as how to find out the optimal temperature for cooking burgers and chicken, the right way to defrost food, the time needed to reheat the food, and the proper floor on which raw meat should be stored in the refrigerator were found lacking. Conclusions: Appropriate training is needed and essential to promote the level of knowledge and ensure that safety is maintained by food-handlers in dealing with food.